PENGARUH BUDAYA ORGANISASI, REWARD DAN INDIVIDUAL CAREER MANAGEMENT TERHADAP KOMITMEN ORGANISASIONAL PEGAWAI PT PLN (PERSERO) UNIT PELAKSANA PEMBANGKITAN TARAHAN - Betty Magdalena; Stefanus Rumangkit; Rakhmat Sandi Putera (Bajang Institute, 2022)
This study aims to determine the effect of Organizational Culture, Rewards, and Individual Career Management on Organizational Commitment. The research uses a quantitative approach with associative methods. The population in this study was the total number of employees of PT PLN (Persero) Tarahan Generation Implementation Unit as many as 106 people, the sample in this study were employees in the field of operation and maintenance as many as 59 people. The data analysis tool uses multiple linear regression, with T test and F test as hypothesis testing. The results showed that Organizational Culture and Rewards did not partially affect the Organizational Commitment of employees of PT PLN (Persero) Tarahan Generation Implementation Unit and Individual Career Management had a partial effect. Another finding from this study is that Organizational Culture, Rewards, Individual Career Management simultaneously have a significant effect on Organizational Commitmen